The Grave Robber : How Jesus can Make your Impossible Possible - Batterson, Mark.; Batterson, Mark. (Grand Rapids, Michigan : Baker Books, a division of Baker Publishing Group, 2014)
Examines "the incredible power of the seven miraculous signs of Jesus found in the Gospel of John. Batterson shows how they were not simply something Jesus did in the past, but something he wants to do now, in the present. He shares true stories of people today who are experiencing miracles in their lives. And he brings to light countless miracles, big and small, that we take for granted every day that point us toward the One who healed the sick, calmed the storm, and yes, even raised the dead"--Amazon.com.
Do we believe that God still does miracles? Do we expect him to move in miraculous ways in our day-in and day-out lives? Maybe we'd like to see miracles, but it's hard to see past our problems. All that is about to change, like water into wine. "There are miracles all around us all the time," says Mark Batterson, "but you won't see them if you don't know how to look for them." Now the bestselling author of The Circle Maker reveals the incredible power of the seven miraculous signs of Jesus found in the Gospel of John. Batterson shows how they were not simply something Jesus did in the past, but something he wants to do now, in the present. He shares true stories of people today who are experiencing miracles in their lives. And he brings to light countless miracles, big and small, that we take for granted every day that point us toward the One who healed the sick, calmed the storm, and yes, even raised the dead. But this is more than a book about miracles. It's a book about the only One who can perform them. Batterson cautions readers, "Don't just seek miracles. Seek Jesus. And if you seek Jesus, miracles will find you." - Amazon.com
Don't miss the miracle. The day water blushed ; Miraculous ; The lost miracles -- The first sign. The wine maker ; Six stone jars ; One nudge -- The second sign. Supernatural synchronicity ; God speed ; The seventh hour -- The third sign. Very superstitious ; Self-fulfilling prophecies ; The rule breaker -- The fourth sign. Two fish ; Lord Algebra ; Count the fish -- The fifth sign. The water walker ; Dare the devil ; Cut the cable -- The sixth sign. Never say never ; The Miracle League ; Spit on it -- The seventh sign. The grave robber ; Even now ; Risk your reputation ; One little yes.
Includes bibliographical references (pages 267-275).
Keywords: Bible. -- Criticism, interpretation, etc; Christian Living -- Biblical teaching; Criticism, interpretation, etc